2021
DOI: 10.3174/ajnr.a7169
|View full text |Cite
|
Sign up to set email alerts
|

MTT Heterogeneity in Perfusion CT Imaging as a Predictor of Outcome after Aneurysmal SAH

Abstract: BACKGROUND AND PURPOSE: Impairment of tissue oxygenation caused by inhomogeneous microscopic blood flow distribution, the so-called capillary transit time heterogeneity, is thought to contribute to delayed cerebral ischemia after aneurysmal SAH but has so far not been systematically evaluated in patients. We hypothesized that heterogeneity of the MTT, derived from CTP parameters, would give insight into the clinical course of patients with aneurysmal SAH and may identify patients at risk of poor outcome. MATER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 38 publications
0
29
0
2
Order By: Relevance
“…The dynamics of quantitative parameters will become increasingly important as a selection criterion in CT perfusion. Therefore, the possibility of more individualized treatment steps will presumably also be investigated [45,46]. TCD is still a helpful additional diagnostic parameter but does not seem to reliable on its own for detecting CVS: Thus, a meta-analysis including 18 studies showed evidence supporting this method only in the case of spasms in the middle cerebral artery [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of quantitative parameters will become increasingly important as a selection criterion in CT perfusion. Therefore, the possibility of more individualized treatment steps will presumably also be investigated [45,46]. TCD is still a helpful additional diagnostic parameter but does not seem to reliable on its own for detecting CVS: Thus, a meta-analysis including 18 studies showed evidence supporting this method only in the case of spasms in the middle cerebral artery [75].…”
Section: Discussionmentioning
confidence: 99%
“…That being said, routine CT perfusion in intubated patients particularly in the high-risk phase, i. e., between day 6 and day 10 after SAH, undoubtedly has significant diagnostic value since hypoperfusion with an endovascular treatment option can be detected to a large extent [44]. Newer studies examined subtle changes in parameter maps between individual follow-up CT perfusion examinations [45,46]. It is clear that better selection of EST based on CT perfusion will be the goal in the future.…”
Section: Role Of Ct Perfusionmentioning
confidence: 99%
“…Furthermore, in studies on cerebral perfusion, MTT is considered a sensitive parameter for the early detection of perfusion defects 21,22 . In addition, MTT is less affected by gray and white matter differences and has been shown to be the most reproducible 21,23 . Therefore, in this study, MTT was chosen as the parameter to evaluate cerebral perfusion in patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were managed according to in-house treatment guidelines, which have been described in previous publications. [18][19][20]…”
Section: Asah Managementmentioning
confidence: 99%
“…While more elaborate examinations such as CT perfusion imaging are available, these have the major disadvantage of lacking standardized procedures for image acquisition and postprocessing, making data from different neurovascular centers often incomparable. 18,[27][28][29][30][31][32] By contrast, native CT imaging is universally used, well-comparable, and also available in low-budget healthcare systems.…”
Section: Improvement Of the Initial Wfns Scoringmentioning
confidence: 99%